Suicide among first-generation and second-generation immigrants in Sweden: association with labour market marginalisation and morbidity. Issue 5 (16th December 2014) - Di Thiene, Domitilla; Alexanderson, K; Tinghög, P; La Torre, G; Mittendorfer-Rutz, E
Abstract : Background: Previous research suggests that first-generation immigrants have a lower suicide risk than those both born in Sweden and with both parents born in Sweden (natives), while the suicide risk in the second generation seems higher. The aim of this study was to investigate to what extent suicide risk in first-generation and second-generation (both parents born abroad) and intermediate-generation (only one parent born abroad) immigrants compared with natives is associated with sociodemographic factors, labour market marginalisation and morbidity. Methods: A prospective population-based cohort study of 4 034 728 individuals aged 16–50 years was followed from 2005 to 2010. HRs for suicide were calculated for first-generation, intermediate-generation and second-generation immigrants compared with natives. Analyses were controlled for sociodemographic factors, morbidity and labour market marginalisation. Results: The HR of suicide was significantly lower in first-generation immigrants (HR 0.83 CI 0.76 to 0.91), and higher in second-generation (HR 1.32, CI 1.15 to 1.52) and intermediate-generation immigrants (HR 1.20, CI 1.08 to 1.33) in comparison to natives. The excess risk was explained by differences in sociodemographics, morbidity and labour market marginalisation. In the fully adjusted models, a higher HR remained only for the Nordic second generation (HR 1.29, CI 1.09 to 1.52). There were no sex differences in HRs. Conclusions: The risk of suicide was shown to be lower in the first generation and higher in the second generation compared with natives. The higher HR in the Nordic second generation was not explained by differences in sociodemographics, labour market marginalisation and morbidity. Further research is warranted to investigate factors underlying this excess risk.